Herpes simplex virus types 1 and 2 homology in the region between 0.58 and 0.68 map units. - Draper, K G (1984)
The homology between herpes simplex virus type 1 and type 2 (HSV-1 and HSV-2, respectively) DNA between 0.58 and 0.674 map units was compared by Southern and dot blot analysis with DNA of one type of virus as a hybridization probe against the other type. Regions of high homology were interspersed with regions of detectably lower homology. However, only one region (between 0.647 and 0.653 map units) contained few or no homologous sequences. In situ RNA blot hybridization demonstrated that the mRNA species transcribed in the right-hand portion of the region are homologous between HSV-1 and HSV-2, as was previously found for the left-hand portion. A 2.7-kilobase HSV-2 transcript in the right-hand portion of the studied region was clearly that encoding HSV-2 glycoprotein C. Comparative nucleotide sequence analysis of specific regions demonstrated that homologous translational reading frames could be identified in the virus types. This analysis also demonstrated that homology could be abruptly lost outside such reading frames. Comparison of regions of homology with published HSV-1 transcription maps suggests that there can also be large divergence within translational reading frames. Some, but not complete, sequence homology was seen in the putative promoter sequence for the 730-base HSV-1 mRNA mapping to the right of glycoprotein C and the corresponding HSV-2 DNA. This suggests that the rather strict conservation of promoter sequences between homologous HSV-1 and HSV-2 transcripts seen in other regions of the genome may not be a necessary feature between these virus types.